THE EFFECTIVENESS OF NEEM OIL Azadirachta indica AGAINST Plutella xylostella LEAF CATERPILLAR ON CABBAGE PLANTS - YULIUS KUNANG; Edy Syahputra; Sarbino Sarbino (Jurnal Sains Pertanian Equator, 2018)
ABSRTACT               Increased production of cabbage plants is often faced with pest problems. Leaf caterpillar Plutella xylostella L. (Lepidoptera: Plutellidae) is a major pest of cabbage plants and if not controlled can decrease both the amount and quality. The use of botanical insecticides is an alternative to controlling        P. xylostella insect pests. This study aims to evaluate the effectiveness of neem oil on P. xylostella pests on cabbage plants. The research was conducted in Subdistrict Rasau Jaya, District Kubu Raya, for 4 months. The research design using Randomized Block Design with 8 treatments and 4 replications. The treatment consisted of 5 levels of neem oil concentration, 2 levels of synthetic insecticides and control. Data analysis using ANOVA was continued by Duncan Mutiple Range Test at 5%. The results showed that the efficacy of neem oil with concentrations of 5, 10, 20, 30 and 40 ml / l of water against (population of         P. xylostella larvae and damage caused by P. xylostella) after application of (76,1% and 43,1%), (66,1% and 23,7%), (66,4% and 31,2%), (68,2% and 22,8%), and (76,2% and 56,5%). Neem oil at concentrations of 20, 30 and 40 ml / l of water exhibit phytotoxicity symptoms.Key words: effectiveness, botanical insecticides, cabbage, neem oil, P. xylostella.